Insight into the current Toxoplasma gondii DNA vaccine: a review article. (31st December 2023) - Zhang, Xirui; Yuan, Hao; Mahmmod, Yasser S.; Yang, Zipeng; Zhao, Mengpo; Song, Yining; Luo, Shengjun; Zhang, Xiu-Xiang; Yuan, Zi-Guo
ABSTRACT: Introduction: Toxoplasma gondii (T.gondii) is a widespread protozoan with significant economic losses and public health importance. But so far, the protective effect of reported DNA-based vaccines fluctuates widely, and no study has demonstrated complete protection. Areas covered: This review provides an inclusive summary of T. gondii DNA vaccine antigens, adjuvants, and some other parameters. A total of 140 articles from 2000 to 2021 were collected from five databases. By contrasting the outcomes of acute and chronic challenges, we aimed to investigate and identify viable immunological strategies for optimum protection. Furthermore, we evaluated and discussed the impact of several parameters on challenge outcomes in the hopes of developing some recommendations to assist better future horizontal comparisons among research. Expert opinion: In the coming five years of research, the exploration of vaccine cocktails combining invasion antigens and metabolic antigens with genetic adjuvants or novel DNA delivery methods may offer us desirable protection against this multiple stage of life parasite. In addition to finding a better immune strategy, developing better in silico prediction methods, solving problems posed by variables in practical applications, and gaining a more profound knowledge of T.gondii -host molecular interaction is also crucial towards a successful vaccine.